Dignitas humana i humanitas christiana w poradniku medytacji Diega de Estella O wzgardzie świata i próżności jego w przekładzie Augustyna Kochańskiego (1611) - Wichowa, Maria (Piśmiennictwo zakonne w dobie staropolskiej, 2013)
The subject of study is human dignity and humanitas christiana interpreted by a Spanish FranciscanDiego de Estella (1524–1578) in his work O wzgardzie świata i próżności jego translated into Polish byanother Franciscian Augustyn Kochański (1568–1632). The book is a meditation guide. In spite of theascetic character of the recommended meditations and Medieval origin of their central idea being decontemptu mundi, the image of the world presented in the book conveys the Renaissance humanitaspropagating the rebirth of the humanity through Jesus Christ (humanitas christiana). Spiritual rebirthof a human being is hereby identified with improving oneself by means of asceticism. The most noblehumanitas and the most perfect form of human dignity is revealed through love for God, through thedivine element within the human soul. A human having been given a universal mind is capable of fullydeveloping his or her humanitas, in this way establishing union with God, achieving spiritual perfectionand eluding inferior forms of life infected by sin.The analysis is made within a relatively broad comparative context. It includes Mateusz Kuligowski’stranslation of the work by M. P. Besse Heraklita chrześcijańskiego albo grzesznie pokutującego lamenta(1694); Wojciech Pakostensis Półgęskowic’s translation of a Spanish Jesuit and teologist Francisco Arias’work entitled Traktat o duchowym postępku (1610); St. Augustine’s Confessions, as well as Thomas àKempis’ The Imitation of Christ. The study proves that in the times when the Church stressed the futilityof life and scorned the vanities of the world, the intellectuals of Renaissance and Baroque put a lot ofeffort in creating the theory of human dignity and humanitatis by propagating the idea of human rebirththrough Christ. Humans having been bestowed with reason and dignity coming from God should turnaway from the world’s vanities and follow the imitationis Christi way.